2020
DOI: 10.31573/vokasi.v15i1.147
|View full text |Cite
|
Sign up to set email alerts
|

Total Bakteri Asam Laktat, Total Asam Tertitrasi dan Tingkat Kesukaan pada Yoghurt Drink dengan Ubi Jalar Ungu sebagai Sumber Prebiotik

Abstract: Karbohidrat utama ubi jalar ungu adalah pati, serat pangan (selulosa, hemiselulosa) serta beberapa jenis gula seperti maltosa, sukrosa, rafinosa, fruktosa dan glukosa. Adanya kandungan karbohidrat dan serat pangan memungkinkan ubi jalar ungu untuk dimanfaatkan sebagai sumber prebiotik baru. Ubi jalar ungu dimanfaatkan sebagai sumber prebiotik pada pangan fungsional (functional food) berupa pangan sinbiotik yaitu yoghurt drink. Penelitian ini bertujuan untuk menentukan aktivitas prebiotik ubi jalar ungu, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…This value indicates that the type of growth media has lower effectiveness when compared to glucose of 2.14 in growing LAB as probiotic candidates, as has been reported in studies discussing sorghum and barley starch (Shaikh et al 2019;Mapengo et al 2021). Imelda et al (2020) report that food is declared a good source of prebiotics if it has an effective value and a prebiotic index above 2.0 (Imelda et al 2020). However, the results showed that MCF acid hydrolysis and debranching pullulanase could stimulate the viability of probiotic LAB, so they were still influential in being developed as prebiotic candidates.…”
Section: Prebiotic Effect and Index Of Mcfmentioning
confidence: 68%
See 3 more Smart Citations
“…This value indicates that the type of growth media has lower effectiveness when compared to glucose of 2.14 in growing LAB as probiotic candidates, as has been reported in studies discussing sorghum and barley starch (Shaikh et al 2019;Mapengo et al 2021). Imelda et al (2020) report that food is declared a good source of prebiotics if it has an effective value and a prebiotic index above 2.0 (Imelda et al 2020). However, the results showed that MCF acid hydrolysis and debranching pullulanase could stimulate the viability of probiotic LAB, so they were still influential in being developed as prebiotic candidates.…”
Section: Prebiotic Effect and Index Of Mcfmentioning
confidence: 68%
“…The prebiotic effect is an increase in the population of probiotic bacteria that occurs constantly without considering the concentration of prebiotics. While the prebiotic index is an increase in the population of probiotic bacteria associated with the concentration of prebiotics ( Imelda et al . 2020 ; Putra 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kandungan glukosa dalam oligosakarida pada ubi jalar kuning akan meningkatkan produksi asam laktat yang dihasilkan akibat metabolisme mikroba pada waktu proses fermentasi berlangsung dan menyebabkan terjadinya penurunan pH. Nilai pH dipengaruhi oleh asam yang dihasilkan, karena peningkatan dari asam laktat akan mengakibatkan semakin banyaknya ion H yang dibebaskan [8,9]. Bertambahnya ion H bebas menyebabkan pH menurun.…”
Section: Hasil Dan Pembahasanunclassified